The effects of load on system and lower-body joint kinetics during jump squats - Moir, G. L.; Gollie, J. M.; Davis, S. E.; Guers, J. J.; Witmer, C. A. (Sports Biomechanics, 2012)
To investigate the effects of different loads on system and lower-body kinetics during jump squats, 12 resistance-trained men performed jumps under different loading conditions: 0%, 12%, 27%, 42%, 56%, 71%, and 85% of 1-repetition maximum (1-RM). System power output was calculated as the product of the vertical component of the ground reaction force and the vertical velocity of the bar during its ascent. Joint power output was calculated during bar ascent for the hip, knee, and ankle joints, and was also summed across the joints. System power output and joint power at knee and ankle joints were maximized at 0% 1-RM ( p , 0.001) and followed the linear trends ( p , 0.001) caused by power output decreasing as the load increased. Power output at the hip was maximized at 42% 1-RM ( p ¼ 0.016) and followed a quadratic trend ( p ¼ 0.030). Summed joint power could be predicted from system power ( p , 0.05), while system power could predict power at the knee and ankle joints under some of the loading conditions. Power at the hip could not be predicted from system power. System power during loaded jumps reflects the power at the knee and ankle, while power at the hip does not correspond to system power.